Management of Noble Morals Education To Build The Soft Skill of Students Through Inquiry Discovery Approach In Biology Learning - Euis Sri Rahmawati; TB Abin Syamsudin; Kingking Muttaqin; Deti Rosmiati (Syntax Corporation Indonesia, 2021)
The focus of this research is The Management of Noble Moral Education to Build Soft Skills of Learners through the Inquiry Discovery Approach in Biology Learning in High School, which is motivated by the fact that although formal schools, both public and private, have been carrying out character education since the enactment of curriculum 2013. However, the study or results of research on character education and noble morals show that so far the management of character education carried out has not referred to the development of noble morals to build soft skills through proper learning design. This research aims to obtain an overview of the management of noble moral education that can build the soft skills of learners through the application of inquiry discovery learning model in biology lessons in high school. The practical benefits of this research can be used as a basis for institutions to improve quality based on the management of noble moral education to build the soft skills of learners through an inquiry discovery approach in biological learning. Theoretically, the results of this study are expected to develop scientific characteristics related to the management of noble moral education to build the soft skills of learners through an inquiry discovery approach in biology learning at SMA Negeri 3 Bandung, and MA Darul Arqam Garut Literature studies are carried out against relevant theories about Education Management, Noble Moral Education, and inquiry discovery leaning approach. The method used is qualitative research that aims to find holistic essential characteristics regarding the management of noble moral education to build the soft skills of learners through an inquiry discovery approach in biological learning. The data collection techniques used in this study are through observation, interview, documentation studies. with research procedures using data analysis methods as well as data triangulation. The general conclusion in this study is that the planning, organizing, implementation, and evaluation of learning in the framework of the application of a discoveri inquiry approach in noble moral education to build the soft skills of learners, can bring up indicators of noble moral components and bring up also aspects of soft skills of learners. 2) The main obstacle felt is the occurrence of pandemic covid-19, which causes students to learn from home, in addition to the current globalization, as well as the hampered support of education funds from the community. The solution is the awareness and approach of educators / educational personnel, PPK implemented in an integrated with each school program, collaborate the participation of parents and teachers to foster the character of students, and improve services through. Especially for pesantren, duisusundan established Emergency Curriculum Supplement refers to the appropriate regulations and guidelines, as well as paying attention to the regulation of. Therefore, it recommends to various parties, among others to the Provincial Education office and the Municipal Education Office, to guide and train educators to have the ability to modify the syllabus and design a learning plan to integrate noble moral education and soft skills to school-level Educational Institutions both principals and school committees as holders and policy makers of education in their schools , to be able to provide guidance and training so that educators are able to organize integrated learning of noble morals that can build the soft skills of learners.